2016
DOI: 10.4103/0973-1296.191451
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extracting solvent on pharmacological activity and cytotoxicity of Polygonum minus, a commonly consumed herb in Southeast Asia

Abstract: Objective:To investigate the antihyperlipidemic, antioxidant, and cytotoxic effect of aqueous and methanol extract of leaves of Polygonum minus.Materials and Methods:Acute antihyperlipidemic effect was studied on chemically induced hyperlipidemic rat model. Treated groups received aqueous and methanol extract of leaves of P. minus respectively (1000 mg/kg; oral) whereas standard treated group received atorvastatin (60 mg/kg; oral) for 3 consecutive days. Blood samples were collected at fixed intervals for lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Increased lipid peroxidation is thought to be a consequence of oxidative stress and it is associated with Alzheimer’s disease [ 52 ]. Our findings can be supported by the preclinical study, which suggested that P. minor extract possessed an antihyperlipidemic effect by significantly reduced lipid levels (total cholesterol, TG, and LDL) in a rat model [ 53 ]. It has been suggested it could be due to the flavonoids myricetin and quercetin that present in the P. minor extract.…”
Section: Discussionsupporting
confidence: 75%
“…Increased lipid peroxidation is thought to be a consequence of oxidative stress and it is associated with Alzheimer’s disease [ 52 ]. Our findings can be supported by the preclinical study, which suggested that P. minor extract possessed an antihyperlipidemic effect by significantly reduced lipid levels (total cholesterol, TG, and LDL) in a rat model [ 53 ]. It has been suggested it could be due to the flavonoids myricetin and quercetin that present in the P. minor extract.…”
Section: Discussionsupporting
confidence: 75%
“…The decreased activity of ALT and AST indicated the hepatoprotective nature of the POLM. The POLM possesses a significant concentration of flavonoids and secondary metabolites, including quercetin, which is believed to be responsible for hepatoprotective activity [ 17 , 61 ]. Farag and El-Rayes [ 62 ] revealed the hepatoprotective effect of quercetin from bee pollen in broilers, which has an ability to restrict oxidative damage to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…P. odorata is a perennial herb that can grow up to 1.0 m in lowlands and 1.5 m in hilly areas. This plant possesses long and lanceolate leaves measuring 0.5–2.0 cm in width and 5–7 cm in length [ 16 , 17 ], and is used traditionally and regularly in Southeast Asian cuisine. P. odorata has many common names, such as Vietnamese cilantro and Vietnamese mint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23,24 Briefly, a total of 20 µl (1000 ppm) of the extract solution or the standard solution was added to 100 µl reagent 25% Folin-Ciolcalteu solution, homogenized for one minute, and allowed for 4 minutes. Then a 75 µl sodium carbonate solution was added and homogenized for one minute.…”
Section: Total Polyphenolic Content Determinationmentioning
confidence: 99%